Strategic HRM, Digital Marketing Capability, and Startup Performance: The Mediating Role of Entrepreneurial Orientation in Generation Z Digital Startups - Nursi, Mulyadi; Risnawati, Henny; Gustiawan, Deni; Kurniawan, Rachmad Risqy (Indonesian Journal of Business and Entrepreneurship Research, 2026)
ABSTRACT This study examines the effect of Strategic Human Resource Management and Digital Marketing Capability on Generation Z Digital Startup Performance, with Entrepreneurial Orientation as a mediating variable. The research addresses the limited integration of organizational capability and entrepreneurial orientation perspectives in explaining startup performance. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data from 200 founders and managers of digital startups in Indonesia. The results indicate that Strategic HRM and Digital Marketing Capability have positive and significant effects on both Entrepreneurial Orientation and startup performance. Entrepreneurial Orientation partially mediates these relationships. The structural model demonstrates strong explanatory power (R² = 0.62) and satisfactory goodness-of-fit indicators. The findings suggest that organizational capabilities must be activated through entrepreneurial orientation to generate superior performance. This study contributes to the development of an integrative capability-based framework within the context of Generation Z digital startups and provides strategic implications for integrated HR and digital marketing management.